Traditional body care of women in Madura Island - Ririn Arisa Putri; Sharyn Graham-Davies; Myrtati Dyah Artaria (Faculty of Social and Political Science, Universitas Airlangga, 2018)
Most of Indonesian family systems adhere to the patriarchy system, in which the husband has the authority to make decision. It is also the case in Prenduan Village in Sumenep region in Madura Island. This research aimed to know how the body care in Prenduan women in Madura, and how the women’s view upon their body cares. It is interesting to see the point of view of women in Madura, whether they do it for themselves, or forthe husbands. This is a qualitative research. We used in-depth interviews and observation to gather the data. We find that body care of Prenduan women in Sumenep, Madura Island has the purpose to make the husband happy and satisfied. For teenage girls, the purpose is for their health, and to prepare them so that they can function well in their family when they get married. They consider using traditional potion is better than those of modern medication made of chemical materials. The focus of the body care practice is the position of a woman as a partner, who is in the position to make the husband happy and satisfied, and also to take care of the family well, in which among the Madura women it is considered as an honor to have such role.